(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
This paper examines the economic efficiency of implementing innovative technologies in the construction materials industry. The study analyzes how technological modernization contributes to reducing production costs, increasing product quality, and improving environmental performance. Using analytical and comparative methods, the research identifies key innovation-driven strategies that enhance productivity and competitiveness. The findings show that the application of digital and eco-efficient technologies in construction materials production provides significant economic advantages, including higher profitability, import substitution, and export potential growth.